The complex world of prince Jǔ anšēr of Caucasian Albania (d. 669) illuminated by the social, cultural, educational, and religious discontinuities of Dawt‘ak K‘ert‘oł’s lament - Cowe, S. Peter (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
This paper explores the representation of prince Jǔ anšēr of Caucasian Albania’s savvy diplomacy on the international scene and consonant maintenance of internal cohesion in the maelstrom transitioning from regional Persian to Arab domination. It argues Dawt‘ak’s lament constitutes a unique early Armenian employment of epideictic rhetoric on a secular theme by a local lay intellectual exposed to higher education (probably in Duin), as suggested by his title of k‘ert‘oł, thereby exemplifying cultural continuity between Utik‘ and Greater Armenia as well as the high caliber of Jǔ anšēr’s court in patronizing such literate culture in parallel with the oral idiom of the gusan bards. The symbiosis of old and new emerges from the poet’s combination of Persianate and Greek norms of masculinity, tensions between the genres of lament and funeral oration and related atmospheric changes from the rational to the emotionally charged. The work also reveals increased Christianizing tendencies through the inclusion of biblical and martyrological topoi together with traditional school disciplines as exemplified by the author’s contemporary Anania Širakac‘i. Similarly, governance is interpreted by the heterogeneous Near-Eastern images of the lion and shepherd, the Hellenic philosopher-king, and in Christocentric mode, thus anticipating the Kamsarakan and later Bagratid models of Christian kingship.